Formative research in curricular plans of public university of Peru - Hidalgo Benites, Lilliam Enriqueta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
A quantitive-qualitative study was carried out with a descriptive, analytical and interpretative design, in which it was investigated whether research occupies a relevant space in the thirty-five curricular plans of the professional careers of a public university of Peru. It was also verified if digital investigative competences were programmed. Finally, It was analysed whether formative research is inserted in the curricula. The sample was census and as an instrument a content analysis matrix was applied to collect information on the previously established study categories. The results reflected diversity in the contents of the curricular plans studied.